The roles of security agencies and media in managing crisis: the simple guidelines / Saidathul Nizah Mat Tazin - Mat Tazin, Saidathul Nizah (Faculty of Communication and Media Studies (FCMS), 2008)
An unexpected scenario seldom occurs in organisations. however, once it strikes, it would possibly be the catastrophic. Organisations or countries for that matter must at least once experience disaster. It may appear in a different nature. Nevertheless, it is still a catastrophe.